Artificial Intelligence Dan Transformasi Perilaku Akademik Mahasiswa Universitas Islam Negeri Sunan Ampel Surabaya Perspektif B. F. Skinner - Arifin, Samsul (Journal of Communication Studies, 2025)
This study aims to explore the role of Artificial Intelligence (AI) in transforming students' academic behavior at the State Islamic University of Sunan Ampel Surabaya through the lens of B.F. Skinner's reinforcement theory. The background of this research focuses on the potential of AI to support learning, while also presenting challenges, particularly concerning academic ethics. This study employs a descriptive qualitative approach with in-depth interviews, observations, and documentation to uncover students' motivations and behavior in using AI. The findings indicate that AI has a dual role as both positive and negative reinforcement in students' academic behavior. Ethical use of AI can enhance independence, engagement in learning, and academic quality. Conversely, AI also has the potential to facilitate unethical academic behaviors through negative reinforcement, such as plagiarism and task completion without deep understanding. This study suggests the importance of implementing positive reinforcement and strict disciplinary measures to encourage responsible AI usage in academic settings.